Measles Virus as a Vector Platform for Glioblastoma Immunotherapy (Review) - E. Yu. Nikolaeva; Yu. R. Shchetinina; I. E. Shokhin; V. V. Zverev; O. A. Svitich; O. Yu. Susova; A. A. Mitrofanov; Yu. I. Ammour (Разработка и регистрация лекарственных средств)
Introduction. Oncolytic virotherapy is one of the approaches in immunotherapy of solid brain tumors. Measles virus vaccine strains are prospective agents for the therapy of cancers such as neuroblastoma, mesothelioma, and glioblastoma multiforme. The hyperexpression of the CD46 and other receptors on the surface of malignant cells allows the measles virus to infect and lyse the tumor, thus inducing an immune response. However, widespread immunization of the population and the resistance of neoplasms to oncolysis present difficulties in clinical practice.Text. This review covers approaches to modifying the measles virus genome in order to increase specificity of virotherapy, overcome existing immunity, and enhance the oncolytic effect. It was shown that expression of proinflammatory cytokines on viral particles leads to tumor regression in mice and triggers a T-cell response. Several approaches have been used to overcome virus-neutralizing antibodies: shielding viral particles, using host cells, and altering the epitope of the protein that enables entry of the virus into the cell. Furthermore, the insertion of reporter genes allows the infection of target cells to be monitored in vivo. A combination with the latest immunotherapies, such as immune checkpoint inhibitors, demonstrates synergistic effects, which suggests the successful use of combined approaches in the therapy of refractory tumors.Conclusion. Measles virus attenuated strains appear to be an easy-to-modify and reliable platform for the therapy of solid brain tumors.